COVID-19 and Food Safety FAQ: Is Coronavirus a Concern with Takeout? (Mandarin Chinese) - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS, 2020)
This is the Mandarin Chinese translation of FSHN20-21/FS349: COVID-19 and Food Safety FAQ: Is Coronavirus a Concern with Takeout?. It provides answers to frequently asked questions regarding COVID-19 and takeout food. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman, and published by the UF/IFAS Food Science and Human Nutrition Department, May 2020.